Game location effect in game-related statistics and pre-shot combination differences between winners and losers during the basketball ACB COVID-19 season - Bustamante-Sánchez, Á.; Jiménez-Saiz, S. L. (PLOS ONE, 2024)
The aim of this study was to assess pre-shot combinations and game-location influence, together with the traditional game-related statistics to evaluate their impact in the performance of the teams in the Asociación de Clubs de Baloncesto (ACB) Spanish basketball league. The COVID-19 season was a great opportunity to better analyse the effect of game-location among ACB-teams to evaluate the differences between winners and losers. A retrospective cross-sectional study of the 2019-2020 ACB season (137 games of the regular season and 33 games of the final stage) was carried out. Game-related statistics were gathered from InStat (https://basketball.instatscout.com/). To evaluate the key performance indicators in this context, a discriminant analysis together with a binary logistic regression were run. The main results revealed that specific variables (normalized per minute played), such as points, field-goal percentage, field goals made, defensive rebounds, assists, and contested field goals made, played a crucial role in classifying winners and losers (p<0.05). Defensive rebounds (0.29±0.05 vs 0.24±0.04, p < 0.001), and assists (0.23±0.05 vs 0.19±0.04, p = 0.042), were key performance indicators for home-court winners. Defensive rebounds (0.29±0.05 vs 0.25±0.04, p < 0.001), and field-goal percentage (48.2±5.31 vs 42.7±5.95, p = 0.009) were key performance variables for away-court winners. Neutral-court winners had better isolation efficiency (49.5±31.6 vs 33.3±31.4, p < 0.05) and contested shot percentage (48.2±6.02 vs 44.8±5.34, p < 0.05) in the context of neutral-court tournaments. Uncontested shots and pick-and-roll efficiency seem not to be so important in the ACB when compared to the (National Basketball Association) NBA. Teams should look for players who assist to good shooters, as well as the presence of specialized players proficient in defensive rebounding. In the context of neutral-court tournaments, the importance of isolations and contested-shot performance is critical.